Macroanatomy, Histomorphometry, and Androgen Receptor Expression in the Epididymis of Kacang Goats Aged 4, 8, and 12 Months - Pratiwi, Herlina; Putra, Diki Purnama; Septian, Wike Andre; Furqon, Ahmad; Suyadi, Suyadi (Universitas Airlangga, 2024)
The epididymis is a crucial component of the goat's reproductive structure. The epididymis is responsible for the transportation, concentration, and maturation of sperm. This study aimed to examine the differences in the structure of macro and microanatomy, tissue composition, and the existence of androgen receptors in the epididymis of Kacang goats aged 4, 8, and 12 months. The assessment of macroscopic organ growth was done immediately after sampling, whereas microscopic measurements were carried out following histological preparations using hematoxylin-eosin (HE) and immunohistochemical (IHC) procedures. The results on the macroscopic anatomy of the epididymis indicated a significant association between age with the width of the caput dexter and sinister and the circumference of the right cauda. However, no significant relationship was found between age with the corpus length and the left cauda's circumference. Significant variations were observed in the diameter and concentration of the agglutinated spermatozoa in the lumen during histomorphometry of the epididymis in three age groups of Kacang goats. There were no statistically significant variations in the expression of androgen receptors among the three age groups. This study showed that the correlation coefficient test reveals a positive relationship between age and the caput width and corpus length dimensions, indicating that these measurements tend to grow as age increases. On the other hand, the diameter of the agglutinated spermatozoa in the epididymal lumen exhibits significant variations between the ages of 4 months, with the ages of 8 months and 12 months, suggesting that the sperm becomes fully matured by the age of 8 months.